2020
DOI: 10.1002/cjoc.201900434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adsorption of ZrO2 in Catalysts on the Efficiency of Hydrolysisof Cellulose to Sugar in Aqueous System under Microwave Radiation

Abstract: Summary of main observation and conclusion Five types of ZrO2 are used to simply establish an effective aqueous catalytic system with sulfuric acid for the hydrolysis of cellulose to sugar, respectively. By adjusting surface roughness and particle size of ZrO2, different adsorption is produced. Accordingly, following the thought to inhibit the self‐aggregation nature of cellulose, after the introduction of ZrO2 with adsorption in catalysts, the efficiency of the hydrolysis of cellulose to sugar is improved. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…That is because the hydroxyl-rich carbon layer-coated CNTs provided rather strong adsorption to break the aggregate structure of cellulose. Accordingly, the acid catalyst can more easily enter the inside of cellulose to enhance the hydrolytic responsiveness of the glycosidic bond. ,, These results showed that the hydroxyl-rich carbon layer on the surface of CNTs played an important role in the hydrolysis of cellulose to sugar.…”
Section: Resultsmentioning
confidence: 95%
“…That is because the hydroxyl-rich carbon layer-coated CNTs provided rather strong adsorption to break the aggregate structure of cellulose. Accordingly, the acid catalyst can more easily enter the inside of cellulose to enhance the hydrolytic responsiveness of the glycosidic bond. ,, These results showed that the hydroxyl-rich carbon layer on the surface of CNTs played an important role in the hydrolysis of cellulose to sugar.…”
Section: Resultsmentioning
confidence: 95%
“…With the diminishing fossil resources and global warming, the utilization of renewable biomass to produce fuels, value‐added chemicals, biomaterials, and prebiotics has attracted great attention. [ 1‐7 ] Sugar alcohols—xylitol, arabitol, and sorbitol, are derived from lignocellulose, which are listed as the 12 most important target chemicals by the US Department of Energy. [ 8 ] Sugar alcohols are the components widely applied in sweets, ice cream fillings, hard candies, sugar‐free chewing gum, moisturizer, softener, and texturizer in food and medical industries.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…ZrO 2 catalyst derived via precipitation demonstrated higher activity; 4.2 and 1.8% yields of 5-HMF and glucose were reached at 523 K and 34.5 MPa. Qiao et al [46,47] investigated cellulose hydrolysis under microwave heating in the presence of oxides at 433 K. The highest total yield of reducing sugars (TRS) was 93.6% in the presence of amorphous ZrO 2 . It should be noted that 0.04 mol L −1 H 2 SO 4 co-catalyst was applied for the activity of solid ZrO 2 based catalysts to be gained.…”
Section: Perspectives Of Zro 2 Catalystsmentioning
confidence: 99%
“…The use of a cocatalyst such as sulfuric acid can improve the efficiency of the dual catalyst system. [46,47] reported glucose yields up to 62.3-91.0% in the presence of two-component system of ZrO 2 + H 2 SO 4 . However, the authors did not discuss the formation of 5-HMF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation